The Potential and Challenges of Implementing the Omnibus Method in Indonesia: Lessons from Other Countries - Prasetyoningsih, Nanik (PDIH Untag Semarang, 2024)
This article seeks to provide an analysis of the issue of over-regulation and the solutions offered by the omnibus method, as well as to examine the application of the omnibus method from a comparative study perspective. The research method employed is normative juridical, using a statutory approach (state approach) and a comparative approach. The data used includes primary data and secondary data, such as relevant legislation and various articles and information from literature sources. The findings indicate that the omnibus method is effective in reducing regulatory burdens, enhancing efficiency, and fostering innovation. In Canada, for instance, implementation through the Budget Implementation Act 2012 led to more responsive policies, although it faced criticism for reducing transparency. In Australia, the Omnibus Repeal Day Bills succeeded in lowering regulatory compliance costs but attracted attention regarding public interest protection. Meanwhile, in the United States, the Consolidated Appropriations Act demonstrated the omnibus method's ability to expedite budget approvals, despite concerns about reduced transparency. In conclusion, although the omnibus method offers promising solutions to address over-regulation, its implementation in Indonesia faces complex challenges, such as low regulatory coordination, resistance to change, and limited public participation. This highlights the importance of an inclusive approach and ongoing evaluation to achieve effective and equitable regulatory reform.